EVALUASI METODE PERHITUNGAN TULANGAN KOLOM DENGAN SOFTWARE TEKLA STRUCTURES DAN AUTODESK REVIT - Maula Al Farizi, Deva; Hapsari, Kartika (Construction and Material Journal, 2025)
Building Information Modeling (BIM) is a technology-driven approach that integrates and manages information from all aspects of a construction project within a comprehensive 3D model. Using BIM-based planning makes the process more efficient, helps minimize over-budget issues, and simplifies volume calculations. There are various BIM software tools such as Autodesk Revit, Tekla Structures, and others, each with its strengths and weaknesses. In this study, the researcher analyzes the Quantity Take-Off (QTO) of the main column reinforcement using Autodesk Revit and Tekla Structures. The results of the rebar QTO from the outputs produced by both software tools showed a total deviation of 0%, indicating that both were equally accurate in generating QTO. This suggests that regardless of the software choice, the accuracy in modeling and managing 3D data remains reliable if the modeling process is done correctly and precisely. Furthermore, QTO calculations using BIM software proved to be more effective, with a result difference of 0.132% compared to conventional methods, as BIM facilitates data processing and automation of changes, directly linked to the 3D model. This ensures that any change in one task automatically adjusts related tasks, thus speeding up the planning and execution process in construction projects.